2013
DOI: 10.5194/bg-10-4073-2013
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effects on carbon-specific respiration rate and sinking velocity of diatom aggregates – potential implications for deep ocean export processes

Abstract: Abstract. Most deep ocean carbon flux profiles show low and almost constant fluxes of particulate organic carbon (POC) in the deep ocean. However, the reason for the non-changing POC fluxes at depths is unknown. This study presents direct measurements of formation, degradation, and sinking velocity of diatom aggregates from laboratory studies performed at 15 °C and 4 °C during a three-week experiment. The average carbon-specific respiration rate during the experiment was 0.12 ± 0.03 at 15 °C, and decreased 3.5… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(97 citation statements)
references
References 69 publications
(55 reference statements)
5
91
1
Order By: Relevance
“…The distinct temperature optima of the transient deepwater surfaceassociated and resident free-living microorganisms provide a reasonable explanation for findings of limited species exchange between particle-associated and free-living microbial communities throughout the water column (104,128,199). It seems likely that the sinking particle-associated microbial communities are composed mainly of microorganisms that originated from surface seawater, and they lose substantial amounts of activity in the cold deep water (200,201). This is consistent with observations that the metabolic activity and growth rate of deepwater surface-associated microbial communities are usually lower than those of the surrounding free-living microbial communities, although the surface-associated microorganisms are almost exclusively responsible for the production and activity of the extracellular hydrolytic enzymes required for nutrient and labile organic matter production from POM.…”
Section: Physiological Challenges and Deleterious Effects Of Microbiamentioning
confidence: 77%
See 1 more Smart Citation
“…The distinct temperature optima of the transient deepwater surfaceassociated and resident free-living microorganisms provide a reasonable explanation for findings of limited species exchange between particle-associated and free-living microbial communities throughout the water column (104,128,199). It seems likely that the sinking particle-associated microbial communities are composed mainly of microorganisms that originated from surface seawater, and they lose substantial amounts of activity in the cold deep water (200,201). This is consistent with observations that the metabolic activity and growth rate of deepwater surface-associated microbial communities are usually lower than those of the surrounding free-living microbial communities, although the surface-associated microorganisms are almost exclusively responsible for the production and activity of the extracellular hydrolytic enzymes required for nutrient and labile organic matter production from POM.…”
Section: Physiological Challenges and Deleterious Effects Of Microbiamentioning
confidence: 77%
“…Thus, extracellular enzymes are likely produced by surface water particlecolonizing microorganisms soon after the colonization event. While the sinking of the particles into deep water will decrease the physiological activity of the particle-associated microorganisms (200), the hydrolytic activities of the secreted extracellular enzymes may be retained (to a large extent), and thus, the resident free-living microorganisms may have a better opportunity to utilize the majority of the nutrients and organic matter released by enzymatic hydrolysis of sinking POM (44,196,197). This "uncoupled" hydrolysis (44,117,206) predicts that the separation of extracellular enzyme activity from the physiological activity of the enzyme producers and the allochthonous particle-associated microbial activity from the autochthonous free-living microbial activity during the sinking of particles from the surface into the deeper waters may have significant implications for microbial functions and biogeochemical processes in the deep ocean.…”
Section: Physiological Challenges and Deleterious Effects Of Microbiamentioning
confidence: 99%
“…Laboratory temperatures were at most ~3 °C warmer than in situ water temperatures which could result in overestimations of sinking speed of up to 15% based on theoretical calculations of the effects of viscosity (Taucher et al 2014). However, observational studies have not observed differences in sinking velocity at different temperatures Iversen and Ploug 2013), so this small difference in temperature is unlikely to bias our measurements. FP were carefully removed from the particle collector tray using a plastic pipette and transferred into a graduated cylinder which was filled with seawater collected from the MSC at the ICE…”
Section: Faecal Pellet Fluxmentioning
confidence: 80%
“…This contradicts the general belief that colonization is the main mechanism determining the attached microbial community at greater depths (43,48). It is, however, possible that other regulating factors, such as quorum sensing (49), viral infection (50), hydrostatic pressure changes (51)(52)(53), and temperature changes (54), had important influences on the outcome of the internal competition between the microbial groups attached to the aggregates, and it will be interesting to use the present method to address those questions.…”
Section: Discussionmentioning
confidence: 99%